IL4-10 fusion protein: a novel immunoregulatory drug combining activities of interleukin 4 and interleukin 10. (11th November 2018) - Steen-Louws, C; Hartgring, S A Y; Popov-Celeketic, J; Lopes, A P; de Smet, M B M; Eijkelkamp, N; Lafeber, F P J G; Hack, C E; van Roon, J A G
Summary: The objective of this study was to test the capacity of a newly developed fusion protein of interleukin 4 (IL-4) and IL-10 [IL4-10 fusion protein (FP)] to shift multiple pro-inflammatory pathways towards immune regulation, and to inhibit pro-inflammatory activity in arthritis models. The effects of IL4-10 FP in comparison with IL-4, IL-10 and IL-4 plus IL-10 on pro- and anti-inflammatory mediators, T cells and immunoglobulin (Ig) receptors in favour of immunoregulatory activity were studied. In addition, the capacity of IL4-10 FP to inhibit pro-inflammatory activity in ex-vivo and in-vivo arthritis models was investigated. IL4-10 FP robustly inhibited pro-inflammatory cytokine [IL-1β, tumour necrosis factor (TNF)-α, IL-6 and IL-8] production in whole blood cultures, mediated by both the IL-10 and the IL-4 moiety. IL4-10 fusion protein induced IL-1 receptor antagonist (IL-1RA) production and preserved soluble TNF receptor (sTNFR) levels, strongly increasing IL-1RA/IL-1β and sTNFR/TNF-α ratios. In addition, IL4-10 FP strongly inhibited T helper (Th) type 1 and 17 cytokine secretion, while maintaining FoxP3 expression and up-regulating Th2 activity. In addition, while largely leaving expression of activating Fc gamma receptor (FcγR)I, III and Fc epsilon receptor (FcεR) unaffected, it significantly shifted the FcγRIIa/FcγRIIb ratio in favour of the inhibitory FcγRIIb. Moreover, IL4–10 FP robustly inhibited secretion of pro-inflammatory cytokines by rheumatoid arthritis synovial tissue and suppressed experimental arthritis in mice, without inducing B cell hyperactivity. IL4-10 fusion protein is a novel drug, signalling cells to induce immunoregulatory activity that overcomes limitations of IL-4 and IL-10 stand-alone therapy, and therefore has therapeutic potential for inflammatory diseases such as rheumatoid arthritis. Graphical Abstract: